Congenital adrenal hyperplasia due to 21-hydroxylase deficiency is associated with a prolonged gestational age. Issue 8 (20th April 2007) - O'Sullivan, Jackie; Iyer, Sriram; Taylor, Norman; Cheetham, Tim
Abstract : Background: The timing of parturition in most mammals is thought to be linked to a late gestational rise in corticosteroid production by the fetal adrenal gland. We hypothesised that gestational age would be prolonged in our patients with impaired cortisol production secondary to congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency. Methods: We compared the gestational age of patients affected by salt-wasting CAH due to 21-hydroxylase deficiency (born 1978–2004; n = 31) with that of children with congenital hypothyroidism (born 1981–2003; n = 30) and a control group of short normal children (born 1980–2002; n = 120). Each group was compared with national (England 2002–3) and regional (2003–4) data on gestational age from hospital episode statistics. Post-term delivery was defined as birth beyond 41 completed weeks. Results: National statistics reveal a frequency of 4.4% for singleton deliveries beyond 41 weeks. In our region the frequency was 4.6%. In the group of children with CAH, the frequency of post-term delivery was 19.3% (p<0.001). In patients with congenital hypothyroidism, the frequency was 13.3% (p = 0.02). The proportion of short children who did not have a recognised endocrinopathy born post term was comparable to national and regional data at 6.7%. Conclusions: A prolonged gestation is more likely in pregnancies where the fetus has the salt-wasting form of CAH. This may be due to impaired cortisol production, although other changes in steroidogenesis may also be contributory.